An investigation of slipping in Rolamite-type mechanisms - Ulozas, Ričardas Viktoras (Strojniški vestnik, 2004)
This paper looks at two variants of slipping that exist in precision roller-band mechanisms (PRBM), such as a Rolamite-type mechanism (geometric and springy slipping). The rollers are wrapped by a flexible band in the mechanisms and contacted between themselves only through a flexible band, the ends of which are attached to the directing planes of the rolamite type mechanism (RTM). In the PRBM there is geometric sliding, the value of which isinfluenced by the thickness of the flexible band. Compensation of the geometric sliding can be achieved by introducing additional band-wrapping rollers, the direction of which is opposite to the main band's direction. The influence of the flexible band's free ends on the accuracy of the positioning of the mechanism is reviewed. The calculation scheme of the mechanism for the measurement and calculation of springy slipping of RTM units is presented and described by equations. It is established that the springy slipping in the RTMis connected to the strain of the free band's pieces from the resistance forces of motion. The value of springy slipping directly depends on the resistance force, the amplitude of motion and the value of the coordinate of the swinging centre. The scheme of a compensator of the springy slipping is presented. The calculation relations permitting us to define the parameters of spring-compensator, eliminating springy slipping, are deduced.
Keywords: mehanizmi Rolamite; zdrsavanje; drsenje oblikovno; drsenje vzmetno; kompenzatorji; transportne naprave; mehanizmi; valj; trak; drsenje